Circulating microRNAs as Biomarkers of Various Forms of Epilepsy - Elena E. Timechko; Kristina D. Lysova; Alexey M. Yakimov; Anastasia I. Paramonova; Anastasia A. Vasilieva; Elena A. Kantimirova; Anna A. Usoltseva; Albina V. Yakunina; Irirna G. Areshkina; Diana V. Dmitrenko (Medical Sciences)
Background: Epilepsy is a group of disorders characterized by a cluster of clinical and EEG signs leading to the formation of abnormal synchronous excitation of neurons in the brain. It is one of the most common neurological disorders worldwide; and is characterized by aberrant expression patterns; both at the level of matrix transcripts and at the level of regulatory RNA sequences. Aberrant expression of a number of microRNAs can mark a particular epileptic syndrome; which will improve the quality of differential diagnosis. Materials and Methods: In this work; the expression profile of six microRNAs was analyzed: hsa-miR-106b-5p; hsa-miR-134-5p; hsa-miR-122-5p; hsa-miR-132-3p; hsa-miR-155-5p; and hsa-miR-206-5p in the blood plasma of patients suffering from temporal lobe epilepsy (n = 52) and juvenile myoclonic epilepsy (n = 42); n—amount of participants; in comparison with healthy volunteers. The expression analysis was carried out using RT-PCR. Mathematical processing of the data was carried out according to the Livak method. Results: A statistically significant change in the expression of hsa-miR-106b-5p; hsa-miR-134-5p; hsa-miR-122-5p; and hsa-miR-132-3p was found. An increase in the expression of hsa-miR-134-5p and hsa-miR-122-5p was registered in the group of patients with temporal lobe epilepsy compared to the control; as well as an increase in the expression of hsa-miR-132-3p and hsa-miR-106b-5p in the juvenile myoclonic epilepsy group compared to the control. hsa-miR-122-5p; 106b-5p; 132-3p are also able to discriminate groups with different syndromes. Additionally; a number of microRNAs are able to discriminate patients with drug-resistant and drug-sensitive forms of epilepsy from the control; as well as patients with hippocampal sclerosis and patients without hippocampal sclerosis from the control. Conclusion. Our data allow us to propose these microRNAs as plasma biomarkers of various epileptic syndromes